An Assessment of The Mahdi Discourse in the Shahkulu Rebellion and Hijri 1000 (Journal of Alevism-Bektashism Studies, 2022)
Throughout the history of Islam, many people who wanted to benefit from the power of the Savior concept declared themselves “Mahdi”. In addition, members of many political formations, religious-mystical groups and sects accepted the leader of the community to which they belonged as Mahdi. The existing powers, political formations/ movements and beliefs that these Mahdis saw as rivals have become a symbol of evil against them. Thereby a tremendous rivalry, representing good and evil, developed between them. In this rivalry, the goal of the leaders or belief leaders, who declared themselves Mahdi, was to eliminate the rival political formations, raise themselves to the dominant position and seize power. This situation has been occurred since the early days of Islam and this kind of cases have always had similar characteristics. Similar methods have been used in most of the rebellions organized around this idea. Shahkulu which occurred in 1511 was undoubtedly manifested by similar ways. This paper will examine the Mahdian aspect of the Shahkulu Rebellion and the methods applied by Shahkulu. The study will have some basic questions in this direction and will make some inferences about the role of the Mahdi discourse in the Shahkulu Rebellion within the scope of these questions. How was the phenomenon of Mahdi understood in 16th-century Islam? Why did the leaders of the 16th-century Islamic states (Ottoman, Safavid and Mughal Empires) and sects use the title Mahdi? How did Shahkulu reach the rank of Mahdi? What metaphors of the Mahdi concept did Shahkulu use? How did Shahkulu utilize Shah Ismail’s charisma for his political interests? The answers to all these questions, which present the basic questions of our study, will be given in the conclusion. Within the scope of the above-mentioned questions, this paper will try to enlighten the effect of Hijri 1000 on the Mahdi concept in the 16th century, the nature that the Mahdi discourse (seen in the Shahkulu Rebellion wich was the first of the Kizilbash uprisings with the Mahdi concept, emerged in the 16th century) gave to the rebellion, and the ground prepared for the next uprisings. Besides, the paper will discuss and compare the main sources, reports, letters and researches by using a descriptive, interpretive and holistic method.